2005
DOI: 10.1007/s10509-005-7667-x
|View full text |Cite
|
Sign up to set email alerts
|

On the Multiplicity of the O-Star Cyg OB2 #8a and its Contribution to the γ-ray Source 3EG J2033+4118

Abstract: Abstract. We present the results of an intensive spectroscopic campaign in the optical waveband revealing that Cyg OB2 #8A is an O6 + O5.5 binary system with a period of about 21.9 d. Cyg OB2 #8A is a bright X-ray source, as well as a nonthermal radio emitter. We discuss the binarity of this star in the framework of a campaign devoted to the study of non-thermal emitters, from the radio waveband to γ-rays. In this context, we attribute the non-thermal radio emission from this star to a population of relativist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…As Cyg OB2 #8A is a binary system, one could wonder whether the existing X‐ray observations reveal a modulation of the X‐ray flux. This issue was first addressed by De Becker et al (2005a) where the results from several X‐ray observations ( ROSAT and ASCA ) were combined to obtain a phase‐folded light curve, on the basis of the ephemeris published by De Becker et al (2004c). The light curve suggested a phase‐locked modulation of the X‐ray flux, probably due to the combined effect of the variation of the absorption along the line of sight and of the X‐ray emission itself as a function of orbital phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Cyg OB2 #8A is a binary system, one could wonder whether the existing X‐ray observations reveal a modulation of the X‐ray flux. This issue was first addressed by De Becker et al (2005a) where the results from several X‐ray observations ( ROSAT and ASCA ) were combined to obtain a phase‐folded light curve, on the basis of the ephemeris published by De Becker et al (2004c). The light curve suggested a phase‐locked modulation of the X‐ray flux, probably due to the combined effect of the variation of the absorption along the line of sight and of the X‐ray emission itself as a function of orbital phase.…”
Section: Discussionmentioning
confidence: 99%
“…We mention that an alternative scenario was proposed by Jardine, Allen & Pollock (1996), but we will assume here that the first‐order Fermi mechanism in the presence of hydrodynamic shocks (the so‐called diffusive shock acceleration–DSA–mechanism) is the dominant process. For a discussion of the physical processes involved in the general scenario of the non‐thermal emission from massive stars, we refer, for example, to De Becker, Rauw & Swings (2005a) and references therein. The issue to be addressed here is that of the nature of these shocks: are they intrinsic to the stellar winds (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, De Becker et al caution that the observed variability might be attributed to systematic effects between XMM-Newton and ROSAT data, as seen in Cyg OB2 No. 8A (De Becker et al 2005a). …”
Section: Colliding-wind Region Between the Supergiant And The Binarymentioning
confidence: 97%
“…De Becker 2005). The putative contribution of some of these early-type stars to the γ-ray source 3EG J2033+4118 has already been discussed by Benaglia et al (2001) and De Becker et al (2005b). In addition, a few long-period Wolf-Rayet binaries (WR 140,WR 146,and WR 147) located close to Cyg OB2 are also classified as non-thermal radio emitters, and may therefore be non-thermal high-energy sources.…”
Section: Introductionmentioning
confidence: 86%